Effect of multiple bluff bodies on hydrogen/air combustion characteristics and thermal properties in micro combustor. (1st February 2023) - Zhang, Yi; Lu, Qingbo; Fan, Baowei; Long, Lin; Quaye, Evans K.; Pan, Jianfeng
Abstract: The bluff body is commonly used to improve micro combustion. The micro combustor with multiple rectangular bluff bodies in a single row was proposed. The effects of bluff bodies on H2 /air combustion characteristics were numerically studied. The temperature distributions, ignition position, combustion efficiency and blow-out limit were investigated via changing the total width and number of bluff bodies. The results show that the combined use of multiple bluff bodies can further expand the blow-out limit of H2 /Air. The effect of high temperature and viscous force on the flow velocity is main factors for the flame morphology. When the total width of bluff bodies is 2 mm, the blow-out limit decreases with the increase of bluff body number. When the total width of bluff bodies is 4 mm and 6 mm, the blow-out limit increases with the increase of the number of bluff bodies. With the increase of inlet velocity, the complete combustion efficiency decreases. The combustion efficiency in the combustor with wider blow-out limit decreases more slowly. It indicates that the combustor with multi-bluff bodies is more suitable for the operation conditions with high flow velocity. Highlights: The effects of multiple bluff bodies on H2 /air micro combustion characteristics. Viscous resistance and flow velocity are dominant on flame morphology. Effect of bluff body's number on blow-out limit at different width is different. Combustor with wider blow-out limit has higher combustion efficiency.